Faculty of Law and Political Sciences - study information - 2001 - PPKE; Radnay József - dean; Deme Erzsébet - edition and layout; Zinner Judit -translated; Anthony Jackson - proof reading; Horváth Gábor - photos; Winter Erzsébet - cover photos; Szent István Társulat (PPKE-JÁK, 2001)
Some Facts about the University; Ideas and Goals; The Educational Structural Units of the Faculty; Book series; Leading Lectures : study information